Prevalence of reduced kidney function and albuminuria in older adults: the Berlin Initiative Study. Issue 6 (9th May 2016) - Ebert, Natalie; Jakob, Olga; Gaedeke, Jens; van der Giet, Markus; Kuhlmann, Martin K.; Martus, Peter; Mielke, Nina; Schuchardt, Mirjam; Tölle, Markus; Wenning, Volker; Schaeffner, Elke S.
Abstract: Background: Although CKD is said to increase among older adults, epidemiologic data on kidney function in people ≥70 years of age are scarce. The Berlin Initiative Study (BIS) aims to fill this gap by evaluating the CKD burden in older adults. Methods: The BIS is a prospective population-based cohort study whose participants are members of Germany's biggest insurance company. This cross-sectional analysis (i) gives a detailed baseline characterization of the participants, (ii) analyses the representativeness of the cohort's disease profile, (iii) assesses GFR and albuminuria levels across age categories, (iv) associates cardiovascular risk factors with GFR as well as albuminuria and (v) compares means of GFR values according to different estimating equations with measured GFR. Results: A total of 2069 participants (52.6% female, mean age 80.4 years) were enrolled: 26.1% were diabetic, 78.8% were on antihypertensive medication, 8.7% had experienced a stroke, 14% a myocardial infarction, 22.6% had cancer, 17.8% were anaemic and 26.5% were obese. The distribution of comorbidities in the BIS cohort was very similar to that in the insurance 'source population'. Creatinine and cystatin C as well as the albumin:creatinine ratio (ACR) increased with increasing age. After multivariate adjustments, reduced GFR and elevated ACR were associated with most cardiovascular risk factors. The prevalence of a GFR <60 mL/min/1.73 m 2 ranged from 38 to 62% depending on the estimation equation used. Conclusions: The BIS is a very well-characterized, representative cohort of older adults. Participants with an ACR ≥30 had significantly higher odds for most cardiovascular risk factors compared with an ACR <30 mg/g. Kidney function declined and ACR rose with increasing age.